Acupuncture and electroacupuncture for stroke: A protocol for overview of systematic review and meta-analysis. Issue 1 (7th January 2022) - Choi, Tae-Young; Ang, Lin; Jun, Ji Hee; Lee, Hye Won; Yun, Jong-Min; Kim, JiHee; Moon, Byung Soon; Joo, Min Cheol; Lee, Myeong Soo
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The aim of this study was to undertake a systematic overview of meta-analyses and published systematic reviews to identify whether and when acupunctureand electroacupuncture are deemed efficacious treatment options for stroke and stroke-related disorders. Methods: Four databases, namely, PubMed, AMED, EMBASE, and the Cochrane Library will be searched from their inception. Two reviewers will independently perform study selection, data extraction, and assessment. This will be followed by an assessment of the methodological and report quality using the Assessment of Multiple Systematic Reviews-2 tool. Finally, the study will entail the assessment of evidence quality by employing the Grading of Recommendations Assessment, Development, and Evaluation system. Results: This overview is expected to provide data on using acupuncture for stroke and stroke-related disorders on the basis of the included systematic reviews' qualitative and quantitative syntheses. Conclusion: This overview will assess the benefits as well as hazards of acupuncture for stroke, subsequently providing patients and practitioners with useful information and have implications for future studies on the topic. Trial registration number: Reviewregistry1263